Glass houses - Haddam, Jane, 1951-2019- (Haddam, Jane, 1951-2019- Gregor Demarkian books, 2007)
Philadelphia has been gripped by a serial killer dubbed by the media as the Plate Glass Killer. Henry Tyder, an alcoholic, often homeless, and member of a socially prominent family on Philadelphias Main Line, has been arrested at the site of the most recent murder after being found covered in the victims blood. Although Tyder has apparently confessed to the crime, his attorney believes him incapable of actually committing the crimes and asks Gregor Demarkian, retired head of the FBIs Behavioral Sciences Unit and fellow-Cavanaugh Street resident, to look into the case. But what could have driven Tyder to confess to crimes he was seemingly incapable of committing? And more importantly, if not him, then who really is the Plate Glass Killer?